Plastic Bag Usage, Inappropriate Disposal and Its Environmental Impacts in Ilorin, Kwara State, Nigeria - M. A. Akanbi-Gada; O. F. Amubieya; O. O. Salami; B. T. Sule; S. T. Olabamiji; A. O. Oyewopo (Journal of Applied Sciences and Environmental Management)
Plastic bag usage and inappropriate disposal have become serious environmental issues, especially in developing nations with sometimes insufficient waste management infrastructure. Hence, the objective of this paper is to survey the plastic bag usage, inappropriate disposal and its environmental impacts in Ilorin, Kwara state, Nigeria by collecting primary data with 100 an online questionnaire. The results were then analyzed and displayed in graphical formats, such as pie charts. According to the poll, 76% of participants said they preferred using plastic bags, and 69% said they used them occasionally. Burning (45%) and open dumping (47%), two disposal techniques that greatly increase environmental contamination, were used. Additionally, 92% of respondents said they were aware of the negative environmental effects of disposing of plastic bags. The findings show that Ilorin has a significant reliance on plastic bags, and that inadequate waste management methods are causing environmental deterioration. The study discovered that although most people are aware of the harm plastic trash does to the ecosystem, inappropriate disposal practices are nevertheless common.